2021
DOI: 10.1523/jneurosci.2306-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Striatal Direct Pathway Targets Npas1+Pallidal Neurons

Abstract: The classic basal ganglia circuit model asserts a complete segregation of the two striatal output pathways. Empirical data argue that, in addition to indirect-pathway striatal projection neurons (iSPNs), direct-pathway striatal projection neurons (dSPNs) innervate the external globus pallidus (GPe). However, the functions of the latter were not known. In this study, we interrogated the organization principles of striatopallidal projections and their roles in full-body movement in mice (both males and females).… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 160 publications
8
29
0
Order By: Relevance
“…Notably, the hypoactivity of STN and arkypallidal GPe neurons was partially alleviated by optogenetic inhibition of prototypic GPe neurons ( Callahan et al, 2021 ). Another recent study identified a subnetwork of direct pathway MSNs specifically targeting arkypallidal Npas-positive neurons in the GPe ( Cui et al, 2021 ). Its role in HD pathogenesis remains to be determined.…”
Section: Striatal Output Structuresmentioning
confidence: 99%
“…Notably, the hypoactivity of STN and arkypallidal GPe neurons was partially alleviated by optogenetic inhibition of prototypic GPe neurons ( Callahan et al, 2021 ). Another recent study identified a subnetwork of direct pathway MSNs specifically targeting arkypallidal Npas-positive neurons in the GPe ( Cui et al, 2021 ). Its role in HD pathogenesis remains to be determined.…”
Section: Striatal Output Structuresmentioning
confidence: 99%
“…3C), electrical stimulation was unlikely to engage all striatal cell types equally. Instead, electrical stimulation was likely biased toward antidromic activation of D1-type dopamine receptor SPNs (D1-SPNs), which are not a canonical source of inhibitory input to the GPe, although they do make some synaptic contacts (12,(15)(16)(17)(18). To test the hypothesis that striatal afferents from D1-SPNs preferentially inhibit Lhx6-GPe neurons, Chronos expression was restricted to D1-SPNs (Fig.…”
mentioning
confidence: 99%
“…One alternative pathway is through the external globus pallidus (GPe). Striatal direct pathway neurons selectively inhibit the Lhx6-positive ( Spix et al, 2021 ) and Npas1-positive ( Cui et al, 2021 ) population of GPe neurons. While there is some overlap between these GPe subtypes ( Abecassis et al, 2020 ), the Lhx6-positive neurons have been shown to inhibit both the dorsal and ventral tier SNc neurons selectively activating GABAA receptors and undergoing strong short-term synaptic depression ( Evans et al, 2020 ).…”
Section: Striatonigral Control Of Dopaminergic Neuronsmentioning
confidence: 99%